Liquiritigenin reduces osteoclast activity in zebrafish model of glucocorticoid-induced osteoporosis - Marta Carnovali; Giuseppe Banfi; Massimo Mariotti (Elsevier, 2020)
Drug and therapies currently used to treat human bone diseases have a lot of severe side effects. Liquiritigenin is a flavonoid extracted from Glycyrrhiza glabra roots which has been reported to have positive effects in vitro on osteoblasts activity and bone mineralization as well as inhibitory effect on osteoclasts differentiation and activity in vitro. The present study was aimed to evaluate the in vivo effects of liquiritigenin on bone structure and metabolism in physiological and pathological conditions using Danio rerio as experimental animal model. Treatments with liquiritigenin were performed on embryos to evaluate the osteogenesis during skeletal development. Other treatments were performed on adult fish affected by glucocorticoid-induced osteoporosis to assay the therapeutic potential of liquiritigenin in the reversion of bone-loss phenotype in scale model. Liquiritigenin treatment of zebrafish embryo significantly enhances the osteogenesis during development in a dose-dependent manner. In addition, liquiritigenin inhibits the formation of the osteoporotic phenotype in adult zebrafish model of glucocorticoid-induced osteoporosis preventing osteoclast activation in scales. Interestingly, liquiritigenin does not counteract the loss of osteoblastic activity in scales. The liquiritigenin exhibits in vivo anti-osteoporotic activity on adult fish scale model. It can be considered a good candidate to develop new drugs against osteoporosis.